The philosophy of Josep Lluís Blasco. The transcendental view - Luque Martín, Víctor J. (Journal of Catalan Intellectual History, 2012)
In this article we will do a survey of the life and works of Josep Lluís Blasco, who was professor of the Theory of Knowledge at the University of Valencia. We will see his relationship with the Marxism and politics during the Transition, the impact of logical positivism and Wittgenstein’s work versus metaphysics in completing his thesis, the impressions from Quine’s work and the challenges of his naturalism, etc. All in all, we will present Josep Lluís Blasco’s change of viewpoint from analytical philosophy to a more Kantian transcendentalism. key words Transcendentalism, metaphysics, Wittgenstein, logical positivism, Quine, analytical philosophy, naturalism, Kant.